Analysis of Lamong Bay Shoreline Changes Use Digital Shoreline Analysis System - Sujantoko; Rikhul Jannah; Mahmud Mustain (Department of Ocean Engineering, 2025)
Lamong Bay is a strategic area, and in 2010 a port was built to improve competitiveness. This study analyzed shoreline changes in the western part of Lamong Bay in 2004, 2009, 2014, 2019, and 2024 using Landsat 7 ETM+ and Landsat 8/9 OLI/TIRS imagery. Data extraction used the Normalized Difference Water Index (NDWI) method in ArcGIS, while shoreline change analysis used the Digital Shoreline Analysis System (DSAS) with End Point Rate (EPR), Net Shoreline Movement (NSM), and Shoreline Change Envelope (SCE). The results show the highest accretion occurred in Romokalisari Village from 2004 to 2009 at 13.80 meters/year, and the highest abrasion occurred in the same village from 2019 to 2024 at -34.21 meters/year. Based on NSM, the highest accretion occurred in Romokalisari from 2004 to 2009 at 67.42 meters, and the highest abrasion occurred from 2019 to 2024 at -163.38 meters. Based on SCE, the highest change occurred in Romokalisari at 331.93 meters from 2019 to 2024, and the lowest change occurred in Osowilangun Village at 0.01 meters in the same period. Overall, accretion dominates the study area, but extreme abrasion in Romokalisari from 2019 to 2024 is influenced by reclamation. This study is expected to support sustainable coastal management and shoreline change mitigation.